Problematika Pelaksanaan Etika Profesi Hakim Dalam Dunia Peradilan - Vinsensius Tamelab; Dwityas Witarti Rabawati; Antonia I. Putri Seran; Maria Viviana Ero Payon (Student Scientific Creativity Journal, 2024)
The legal profession is one of the professions that requires its members to fulfill moral values. The main criterion for being an organizer of the legal profession in upholding the law lies in the independence of professional organizers and the strength of moral integrity in facing various problems under their responsibility. To be a good organizer of the legal profession in carrying out its professional duties in upholding the law requires practitioners who have qualifications of attitude, humanitarian attitude, attitude of justice, able to see and place objective values in a case handled, honest attitude, and have technical skills and ethical maturity. the code of ethics of the legal profession actually functions as an ethical controller for those who carry out the legal profession. According to the ethics of the legal profession, legal professionals are expected to possess certain critical individual abilities. The judge, as the main element of the judiciary, places his profession as the representative of God, because the judge's task is to determine law and justice in society, so the responsibility he carries is very heavy but noble. Therefore, with such great power given to the judicial profession, judges are required to have a balanced attitude, full of responsibility to their conscience and ethical values toward their profession. However, when we look at the current reality, there are many problems that arise. There are many cases of judges violating the code of ethics.